Herbal therapy for ameliorating nonalcoholic fatty liver disease via rebuilding the intestinal microecology - Xiao-Fang Yang; Ming Lu; Lijiao You; Huan Gen; Lin Yuan; Tianning Tian; Chun-Yu Li; Kailiang Xu; Jie Hou; Ming Lei (BMC, 2021)
Abstract The worldwide prevalence of nonalcoholic fatty liver disease (NAFLD) is increasing, and this metabolic disorder has been recognized as a severe threat to human health. A variety of chemical drugs have been approved for treating NAFLD, however, they always has serious side effects. Chinese herbal medicines (CHMs) have been widely used for preventing and treating a range of metabolic diseases with satisfactory safety and effective performance in clinical treatment of NAFLD. Recent studies indicated that imbanlance of the intestinal microbiota was closely associated with the occurrence and development of NAFLD, thus, the intestinal microbiota has been recognized as a promising target for treatment of NAFLD. In recent decades, a variety of CHMs have been reported to effectively prevent or treat NAFLD by modulating intestinal microbiota to further interfer the gut-liver axis. In this review, recent advances in CHMs for the treatment of NAFLD via rebuilding the intestinal microecology were systematically reviewed. The key roles of CHMs in the regulation of gut microbiota and the gut-liver axis along with their mechanisms (such as modulating intestinal permeability, reducing the inflammatory response, protecting liver cells, improving lipid metabolism, and modulating nuclear receptors), were well summarized. All the knowledge and information presented here will be very helpful for researchers to better understand the applications and mechanisms of CHMs for treatment of NAFLD.